Structural insights into transcription initiation by yeast RNA polymerase I - Sadian, Yashar; Beck, Martin; Müller, Christoph W. (The EMBO journal, 2017)
In eukaryotic cells, RNA polymerase I (Pol I) synthesizes precursor ribosomal RNA (pre‐rRNA) that is subsequently processed into mature rRNA. To initiate transcription, Pol I requires the assembly of a multi‐subunit pre‐initiation complex (PIC) at the ribosomal RNA promoter. In yeast, the minimal PIC includes Pol I, the transcription factor Rrn3, and Core Factor (CF) composed of subunits Rrn6, Rrn7, and Rrn11. Here, we present the cryo‐EM structure of the 18‐subunit yeast Pol I PIC bound to a transcription scaffold. The cryo‐EM map reveals an unexpected arrangement of the DNA and CF subunits relative to Pol I. The upstream DNA is positioned differently than in any previous structures of the Pol II PIC. Furthermore, the TFIIB‐related subunit Rrn7 also occupies a different location compared to the Pol II PIC although it uses similar interfaces as TFIIB to contact DNA. Our results show that although general features of eukaryotic transcription initiation are conserved, Pol I and Pol II use them differently in their respective transcription initiation complexes.
Gesehen am 08.10.2018